Socio-Economic Impact of the Imposed Lockdowns in Food Chains: A Case Study in Cyprus - Koumoulidis, Dimitrios; Katsenios, Nikolaos; Kasimatis, Christoforos-Nikitas; Xydis, George; Efthimiadou, Aspasia (My University, 2022)
COVID-19 has affected the entire existence of humans. Despite the mass vaccination programs globally deployed, some governments are still struggling to minimize human losses, high rates of virus transmission, and the socio-economic shock the entire planet has being gone through. COVID-19 has seriously affected all global socio-economic sectors. In this direction, agriculture, food-security and the environment could not be outside of the high-scale negative impacts, especially during the first year of the imposed lockdowns on both national and global scales. The present study provides information on the impact of COVID-19 and the lockdowns imposed, having as its study area the Republic of Cyprus. The study focuses on potato cultivation and production, and on which level entire agricultural procedures were affected during the examined period of the lockdown. A survey methodology study was done with questionnaires distributed to local potato farmers across the country to quantify and identify the link between the pandemic and the potato sector of the island. It was revealed that manpower was limited due to the lockdowns, the distribution of crops to markets disrupted, long delays in transactions in the agricultural sector were experienced, and economic uncertainty, in general, in Cyprus was experienced, among other impacts. Results of the study indicated that—since COVID-19 is not going to be the last disease—a global transition towards a more resilient and spatially localised food network is required.
Keywords: COVID-19; potato-sector; Cyprus; Lockdowns; Agriculture; Potato-sector; Questionnaires; Cyprus